Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to find the general solution of the DE $y''+y=x$ with a Maclaurin series. I know that I could solve this using the Principle of Superposition by finding a particular solution and the general solution to the homogeneous $y''+y=0$ (which yields the solution $y=acosx+bsinx+x$) but I am looking for what I am doing wrong.

If we let $y=\sum_{n=0}^{\infty}c_nx^n$ then, by substituting into the original DE we can obtain a recursive relation. After substituting and rearranging I obtained:$$2c_2+c_0+[6c_3+c_1]x+\sum_{n=2}^{\infty}c_{n+1}(n+2)(n+1)+c_n=0+x+\sum_{n=2}^\infty0$$ This gives the recurrence relation $$c_{n+2}=-\frac{c_n}{(n+2)(n+1)}, n>1$$ and the relationships $2c_2+c_0=0$ and $6c_3+c_1=1$ which allows us to solve $c_2$ and $c_3$ in terms of $c_0$ and $c_1$: $c_2=-\frac{c_0}{2}$, $c_3$=$-\frac{c_1-1}{6}$.

The solution for the recurrence relation is given by $$c_{2n}=(-1)^n\frac{c_0}{(2n)!}, c_{2n+1}=(-1)^n\frac{c_1-1}{(2n+1)!},n\in\mathbb{Z}^+$$

However, if I substitute these solutions into the assumed form $$\sum_{n=0}^{\infty}c_nx^n=\sum_{n=0}^{\infty}c_{2n}x^{2n}+\sum_{n=0}^{\infty}c_{2n+1}x^{2n+1}$$ we obtain the Maclaurin series for $cosx$ and $sinx$ but no $x$. What happened to the $x$? What did I do wrong?

share|cite|improve this question

Hint: If you had $c_1$ instead of $c_1-1$ in your formula for $c_{2n+1}$, then you would really get $\sin x$ without $x$. But now you have to check carefully what that "$-1$" does...

share|cite|improve this answer
Yes, I forgot to mention that but wouldn't we just group the constants together? So we write $c_1-1=c_2$? – Hautdesert Apr 18 '12 at 23:04
@Hautdesert: you can't do that since $c_1-1=b$ with $b$ the constant of the $\sin(x)$. – Raymond Manzoni Apr 18 '12 at 23:12
Well, I really do not understand what I am missing then. What am I supposed to do with that -1? I've been trying to get this for a while now but nothing comes to mind. – Hautdesert Apr 18 '12 at 23:37
@Hautdesert: just set $b:=c_1−1$ then the odd terms of $y$ will give you $c_1 x+c_3 x^3+c_5 x^5 −\cdots = (b+1)x - b \dfrac{x^3}{3!} +b \dfrac{x^5}{5!}-\cdots= b\sin(x) + x\ $ (sorry for the edits...) – Raymond Manzoni Apr 18 '12 at 23:49

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.